Transtibial Versus Anteromedial Portal ACL Reconstruction: Is a Hybrid Approach the Best?. Issue 8 (28th July 2017) - Jennings, Jonathan K.; Leas, Daniel P.; Fleischli, James E.; D'Alessandro, Donald F.; Peindl, Richard D.; Piasecki, Dana P.
Background: Improved biomechanical and clinical outcomes are seen when the femoral tunnels of the anterior cruciate ligament (ACL) are placed in the center of the femoral insertion. The transtibial (TT) technique has been shown to be less capable of this than an anteromedial (AM) portal approach but is more familiar to surgeons and less technically challenging. A hybrid transtibial (HTT) technique using medial portal guidance of a transtibial guide wire without knee hyperflexion may offer anatomic tunnel placement while maintaining the relative ease of a TT technique. Purpose: To evaluate the anatomic and biomechanical performance of the HTT technique compared with TT and AM approaches. Study Design: Controlled laboratory study. Methods: Thirty-six paired, fresh-frozen human knees were used. Twenty-four knees (12 pairs) underwent all 3 techniques (TT, AM, HTT) for femoral tunnel placement, with direct measurement of femoral insertional overlap and femoral tunnel length. The remaining 12 knees (6 pairs) underwent completed reconstructions to evaluate graft anisometry and tunnel orientation, with each technique performed in 4 specimens and tested using motion sensors with a quad-load induced model. Graft length changes and graft/femoral tunnel angle were measured at varying degrees of flexion. Results: Percentage overlap of the femoral insertion averaged 37.0% ± 28.6% for TT, 93.9% ± 5.6% for HTT, and 79.7% ± 7.7% for AM, with HTT significantly greater than both TT ( P = .007) and AM ( P = .001) approaches. Graft length change during knee flexion (anisometry) was 30.1% for HTT, 12.8% for AM, and 8.5% for TT. When compared with the TT approach, HTT constructs exhibited comparable graft–femoral tunnel angulation (TT, 150° ± 3° vs HTT, 142° ± 2.3°; P < .001) and length (TT, 42.6 ± 2.8 mm vs HTT, 38.5 ± 2.0 mm; P = .12), while AM portal tunnels were significantly shorter (31.6 ± 1.6 mm; P = .001) and more angulated (121° ± 6.5°; P < .001). Conclusion: The HTT technique avoids hyperflexion and maintains femoral tunnel orientation and length, similar to the TT technique, but simultaneously achieves anatomic graft positioning. Clinical Relevance: The HTT technique offers an anatomic alternative to an AM portal approach while maintaining the technical advantages of a traditional TT reconstruction.